2015
DOI: 10.11648/j.ajhr.20150304.14
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Male Partner’s Involvement in Prevention of Mother-to-Child Transmission of HIV and Associated Factors Among Males in PMTCT Services

Abstract: Background: Maintaining an adequate and safe Prevention Mother-to-Child Transmission of HIV services and male partner's involvement in PMTCT services are an issue of concern to local health planner especially with increase in population size and an increase in the number of medical facilities. Objectives: To describes whether methodological issues such as sample Characteristics, Outcome measures, and mechanisms causing change in the outcome measures could explain some of the inconsistent findings evident on. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 29 publications
1
5
1
Order By: Relevance
“…This finding is consistent with the study conducted in Kibaale District, Uganda [7]. The referred study revealed that African men have been found to hold onto certain traditional cultural beliefs which inhibit their active involvement in reproductive health programmes [24][25][26][27].…”
Section: Discussionsupporting
confidence: 89%
“…This finding is consistent with the study conducted in Kibaale District, Uganda [7]. The referred study revealed that African men have been found to hold onto certain traditional cultural beliefs which inhibit their active involvement in reproductive health programmes [24][25][26][27].…”
Section: Discussionsupporting
confidence: 89%
“…In our study area there are few public and very limited private health institutions that provide PMTCT of HIV service. In contrast, the finding is higher than a study conducted in Mwanza District, Malawi which had 13.7% of males involved in PMTCT of HIV service [14]. The difference could be related to difference in study period, information education communication and behavioral change in communication, since male involvement on PMTCT of HIV services is increased time to time due to mass media and health care provider's awareness creation effort.…”
Section: Discussioncontrasting
confidence: 59%
“…Studies conducted in Thailand, Uganda, Kenya, Mekelle Ethiopia and Gondar Ethiopia showed that the prevalence of male involvement in the PMTCT of HIV were 46%, 5%, 31%, 20.1%, and 27.3%, respectively [7][8][9][10][11]. Age, residence, marital status, educational level, occupational status, average monthly income, and distance from the health institution were the significant risk factors for the PMTCT of HIV in a previous studies [12][13][14][15].…”
Section: Introductionmentioning
confidence: 94%
“…However, male involvement in the PMTCT program remains low in low and middle-income countries, including Ethiopia [10,11]. For instance, a study conducted in the Myanmar region of Asia revealed that male involvement in PMTC is 13% [12], A Brief Review of Initiatives in East, West and Central Africa showed that male involvement in PMTCT was low with a range from 1.8 to 32% [13].…”
mentioning
confidence: 99%
“…For instance, a study conducted in the Myanmar region of Asia revealed that male involvement in PMTC is 13% [12], A Brief Review of Initiatives in East, West and Central Africa showed that male involvement in PMTCT was low with a range from 1.8 to 32% [13]. Another systemic review conducted in Ethiopia showed that male involvement in PMTCT was 14 to 30% [11]. Recent studies on the topic suggest that there were several reasons for the low level of male involvement, including cultural barriers and norms, PMTCT/ANC knowledge, sociodemographic characteristics, male individual factors and health system [13][14][15].…”
mentioning
confidence: 99%